Interface-mediated spontaneous symmetry breaking and mutual communication between drops containing chemically active particles - D. P. Singh (Nature Portfolio, 2020)
Complex systems exhibit unique properties like spontaneous symmetry breaking and self-organization. Singh et al. show that catalytically active, non-propelling particles can induce steady vortical flows within a drop, as well as flow alignment between neighboring drops.